KEBERTAHANAN KULTURAL DAN RELIGI DI AREA PERMUKIMAN TERDAMPAK BENCANA LUMPUR LAPINDO SIDOARJO, JAWA TIMUR - June Ekawati (Sabda: Jurnal Kajian Kebudayaan, 2018)
Indonesia is a disaster-prone country, therefore efforts for Disaster Risk Reduction are very useful to do.This paper aims to examine the cultural and religious roles of settlement in areas affected by the Lapindo mudflow disaster in Sidoarjo. The method used in this study is the study of relevant literature from research that has been done before. From the results of the literature review, it was concluded that culture and religion became capital for the people who were maintained even though their settlements were now scattered. Culture and religion also become identities which are very influential factors for the resilience of settlements which up to now still have vulnerability, so that anticipation and adaptation need to be carried out as preparedness for possible future disasters.